Preparation method and application of polygonal hollow carbon structure loaded with Cu and Pd diatomic nano-enzymes

CN122874487APending Publication Date: 2026-10-09GUANGXI MEDICAL UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610946587.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-29
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

但是,载体导电性差;制备依赖液氮冷冻与光还原,工艺复杂、能耗高,不利规模化;仅适用于电催化体系,需外加电能,无法常温常压自发催化;未涉及硫、氟杂原子引入

Benefits of technology

1、本申请的多边形中空碳结构具有极高的比表面积和丰富的孔隙通道,能够暴露更多的金属活性位点,增加了反应物与活性位点的接触机会。而现有技术均采用常规实心或二维平面负载结构,活性位点暴露程度有限,制约了催化性能的进一步提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122874487A_ABST
    Figure CN122874487A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method and application of a Cu and Pd loaded diatomic nanoscale enzyme of a polygonal hollow carbon structure, and relates to the technical field of nanoscale enzyme catalytic materials. The preparation method of the nanoscale enzyme comprises the following steps: synthesizing an organic ligand BIM by reacting hydrazine monohydrate and 4-methyl imidazole; dissolving copper acetylacetonate, palladium acetylacetonate, zinc nitrate hexahydrate, sodium formate, oleylamine and BIM in DMF to obtain a precursor by reaction; and obtaining the Cu and Pd loaded diatomic nanoscale enzyme by pyrolysis of the precursor under an argon atmosphere. The nanoscale enzyme has a polygonal hollow porous structure, and has POD-like activity and GSHOx-like activity; the nanoscale enzyme can continuously generate hydroxyl radicals (·OH) and consume GSH in bacteria, thereby efficiently destroying bacterial biofilms to effectively kill MRSA, and providing a new strategy for the treatment of drug-resistant bacterial infectious osteomyelitis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nanozyme catalytic materials technology, specifically to a method for preparing and applying a diatomic nanozyme supported on Cu and Pd in ​​a polygonal hollow carbon structure. Background Technology

[0002] Infectious osteomyelitis, especially the type caused by methicillin-resistant Staphylococcus aureus (MRSA), poses a significant challenge to orthopedic clinical treatment due to its high recurrence rate and widespread resistance to traditional antibiotics. MRSA can form a dense bacterial biofilm on bone tissue and implant surfaces, hindering antibiotic penetration and evading the immune system's clearance, leading to persistent infection. Current clinical treatment primarily involves long-term, high-dose antibiotics combined with surgical debridement, but its efficacy is limited and it easily causes systemic toxicity and the development of drug-resistant bacteria. Therefore, there is an urgent need to develop a highly effective and controllable non-antibiotic therapy.

[0003] In recent years, nanozymes have shown great potential in various fields due to their enzyme-like catalytic activity, high stability, and tunability. For example, Chinese invention patent application CN113786843A (published on December 14, 2021) discloses a palladium-iron bimetallic cluster nanozyme supported on nanocarbon, its preparation method, and its applications. In this invention, the palladium-iron bimetallic nanozyme exists in atomically dispersed clusters, improving atom utilization. Simultaneously, the palladium-iron bimetallic nanozyme exhibits synergistic catalytic activity, showing significantly improved enzyme catalytic activity compared to palladium-iron monometallic nanozymes. The palladium-iron bimetallic cluster nanozyme prepared by this invention has a simple and easy preparation process, and the reaction process is easily controlled. Furthermore, the prepared nanocarbon-supported palladium-iron bimetallic cluster nanozyme can catalyze the decomposition of oxygen in the air to generate hydroxyl radicals (·OH) under acidic conditions at room temperature without the need for external light or electricity, thereby effectively killing bacteria. The palladium-iron bimetallic cluster nanozyme exhibits excellent catalytic antibacterial performance and has broad application prospects in the future antibacterial field. However, the support is nanocarbon, which has a chemically inert surface, and the metal... The carriers have weak interactions and are prone to aggregation and deactivation with long-term use; they lack non-metallic heteroatom doping and have insufficient electronic structure control capabilities; their conventional solid structure limits their specific surface area and mass transfer efficiency.

[0004] For example, Chinese invention patent application CN117860780A (publication date: July 30, 2024) discloses a PdCu diatomic modified carbon nitride catalyst material, its preparation method, and its application. The method involves first performing a secondary pyrolysis of a carbon nitride precursor to obtain a supported carbon nitride material. Then, a Pd precursor solution and a Cu precursor solution of a certain concentration are prepared and added to the carbon nitride solution in a specific ratio to form a mixed liquid. The mixed liquid is then rapidly frozen in liquid nitrogen and gradually thawed under xenon lamp irradiation. After filtration, washing with water, and drying, the PdCu diatomic modified carbon nitride catalyst material is obtained. In this catalyst material, PdCu exists in a highly dispersed form. Both Pd and Cu are reactive sites, and they coordinate to regulate the formation and desorption of the intermediate (*OOH), promoting the electrocatalytic production of hydrogen peroxide. Furthermore, the electrocatalytic hydrogen peroxide production performance was tested using a rotating ring electrode electrode (RRDE), yielding considerable selectivity, which is beneficial for further dispersed electrocatalytic hydrogen peroxide production. However, the carrier has poor conductivity; the preparation relies on liquid nitrogen freezing and photoreduction, which is complex and energy-intensive, making it unsuitable for large-scale production; it is only applicable to electrocatalytic systems, requiring external power, and cannot spontaneously catalyze at room temperature and pressure; and it does not involve the introduction of sulfur or fluorine heteroatoms.

[0005] In summary, existing nanozyme materials still suffer from several technical drawbacks, including the limited structure of the carrier material; the limited means of regulating the elemental composition and electronic structure of the metal active center, making it difficult to fully leverage the synergistic catalytic effect of multiple metals; and the complex preparation methods, which are not conducive to large-scale preparation. Summary of the Invention

[0006] To address the problems existing in current nanozymes, this invention provides a diatomic nanozyme with a polygonal hollow carbon structure loaded with Cu and Pd (hereinafter referred to as CuPd nanozyme). SF The / YSHNC nanozyme contains uniformly distributed C, N, O, Cu and Pd elements.

[0007] Furthermore, the atomic percentage of C in the Cu and Pd loaded diatomic nanozyme is 85%~95%, the atomic percentage of N is 2%~6%, the atomic percentage of O is 5%~10%, the atomic percentage of Cu is 1%~3%, and the atomic percentage of Pd is 0.05%~0.3%.

[0008] Furthermore, the Cu and Pd loaded diatomic nanozyme has a polygonal hollow porous structure; The nanozyme has an outer diameter of 40-50 nm, an inner cavity diameter of 15-20 nm, and a specific surface area of ​​800-1000 m² / g.

[0009] Furthermore, the Cu and Pd loaded diatomic nanozymes possess at least one of POD-like activity and GSHOx-like activity.

[0010] This application also provides a method for preparing a two-atom nanozyme with a polygonal hollow carbon structure loaded with Cu and Pd, comprising the following steps: Step S1: Dissolve 0.5-1.0 g of hydrazine monohydrate in 10-15 mL of methanol, and dissolve 1.5-2.0 g of 4-methylimidazole in 30-40 mL of methanol. After mixing, heat in an oil bath at 55-75℃ with stirring. After naturally cooling to room temperature, let stand for 2-6 h, collect the solid by centrifugation, wash with methanol, and dry to obtain the organic ligand BIM. Step S2: Dissolve 3-5 mg of copper acetylacetonate, 1-3 mg of palladium acetylacetonate, 0.4-0.8 g of zinc nitrate hexahydrate, 20-40 mg of sodium formate, 5-10 mL of oleylamine, and 0.2-0.5 g of the BIM in 200-300 mL of N,N-dimethylformamide. Stir and heat in an oil bath, allow to cool naturally to room temperature, and let stand for 2-6 h. Collect the solid by centrifugation, wash with N,N-dimethylformamide, and dry to obtain the precursor STU1-b. Step S3: After heat treatment, the precursor STU1-b is naturally cooled and then ground to obtain the Cu and Pd loaded diatomic nanozyme.

[0011] Furthermore, in step S1, the oil bath stirring and heating time is 12-18 hours, and the drying temperature is 60-100℃.

[0012] Furthermore, in step S2, the temperature of the oil bath is 100-120℃, the oil bath stirring and heating time is 48-72 h, and the drying temperature is 60-100℃.

[0013] Furthermore, the heat treatment conditions in step S3 are as follows: under an argon atmosphere, the heat treatment temperature is 600-900℃, and the heat treatment time is 4-8 h.

[0014] Furthermore, in step S1, the methanol washing is performed 3-5 times; in step S2, the N,N-dimethylformamide washing is performed 3-5 times.

[0015] This application also provides the use of a Cu and Pd loaded diatomic nanozyme in the preparation of a therapeutic drug for drug-resistant bacterial osteomyelitis.

[0016] Compared with existing technologies, the advantages and effects of this application are as follows: 1. The polygonal hollow carbon structure of this application has an extremely high specific surface area and abundant pore channels, which can expose more metal active sites and increase the contact opportunities between reactants and active sites. In contrast, existing technologies all use conventional solid or two-dimensional planar supported structures, which have limited exposure of active sites and restrict further improvement of catalytic performance.

[0017] 2. Existing nanozymes still suffer from drawbacks such as complex preparation processes, reliance on specialized equipment, and cumbersome post-processing. In contrast, this application employs a high-temperature pyrolysis method, which simplifies the preparation process, makes it easy to operate, and requires only simple grinding for post-processing, eliminating the need for cumbersome steps such as acid washing. This method is low-cost, highly efficient, and environmentally friendly. 3. Existing antibacterial nanozymes are multifunctional but limited in scope, have poor efficacy against drug-resistant bacteria, and lack the ability to disrupt biofilms. The polygonal hollow carbon structure-loaded Cu and Pd diatomic nanozymes prepared in this application have POD-like and GSHOx-like activities. They can efficiently catalyze the generation of hydroxyl radicals to disrupt bacterial biofilm structures and consume glutathione to weaken the bacteria's own antioxidant defense system, thereby efficiently killing MRSA and showing promise for treating infectious osteomyelitis.

[0018] 4. CuPd prepared by the preparation method provided in this application SF / YSHNC nanozyme at 20 μg / mL can achieve a sterilization rate of 99.9%, indicating that CuPd SF / YSHNC nanozymes can efficiently kill MRSA, exhibiting excellent in vitro antibacterial activity.

[0019] 5. Evaluation of CuPd nanozyme using a GSH kit SF The ability of / YSHNC to digest glutathione (GSH) in bacteria indicates that the CuPd in ​​this application... SF The GSH content in the / YSHNC nanozyme decreased by approximately 36.4% compared to the control group, indicating that CuPd SF / YSHNC nanozymes can efficiently consume GSH in bacteria, thereby disrupting the redox homeostasis of bacteria.

[0020] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, the preferred embodiments of this application are described in detail below with reference to the accompanying drawings.

[0021] The above and other objects, advantages and features of this application will become more apparent to those skilled in the art from the following detailed description of specific embodiments in conjunction with the accompanying drawings. Attached Figure Description

[0022] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort. In all drawings, similar elements or parts are generally identified by similar reference numerals. In the drawings, the elements or parts are not necessarily drawn to scale.

[0023] in: Figure 1 This is a schematic flowchart of the preparation method of this application; Figure 2 CuPd SF Transmission electron microscopy (TEM) image of / YSHNC nanozyme, Bar=50 nm; Figure 3 CuPd SF Mapping analysis results of / YSHNC nanozymes: a is bright field, b is a schematic diagram of C atom distribution, c is a schematic diagram of N atom distribution, d is a schematic diagram of O atom distribution, e is a schematic diagram of Cu atom distribution, f is a schematic diagram of Pd atom distribution, Bar=100 nm. Figure 4 CuPd SF EDS spectrum of YSHNC nanozyme; Figure 5 CuPd SF Figure 1. BET analysis results of YSHNC nanozyme; Figure 6 CuPd SF Schematic diagram of the POD-like activity detection results of / YSHNC nanozymes; Figure 7 CuPd SF Schematic diagram of the GSHOx-like activity detection results of / YSHNC nanozymes; Figure 8 CuPd SF / Schematic diagram of the detection results of the digestive capacity of YSHNC nanozyme against glutathione (GSH) in bacteria; Figure 9 CuPd SF A schematic diagram of the in vitro antibacterial activity detection results of / YSHNC nanozyme, where a is the 0 μg / mL group, i.e., the control group; b is the 2.5 μg / mL group; c is the 5 μg / mL group; d is the 10 μg / mL group; e is the 15 μg / mL group; and f is the 20 μg / mL group. Figure 10 CuPdSF A schematic diagram of the anti-biofilm activity detection results of / YSHNC nanozymes, where a is the 0 μg / mL group, i.e., the control group; b is the 2.5 μg / mL group; c is the 5 μg / mL group; d is the 10 μg / mL group; e is the 15 μg / mL group; and f is the 20 μg / mL group. Detailed Implementation

[0024] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. In the following description, specific details such as specific configurations and components are provided merely to help fully understand the embodiments of this application. Therefore, those skilled in the art should understand that various changes and modifications can be made to the embodiments described herein without departing from the scope and spirit of this application. In addition, for clarity and brevity, descriptions of known functions and structures are omitted in the embodiments.

[0025] It should be understood that the phrase "an embodiment" or "this embodiment" throughout the specification means that a specific feature, structure, or characteristic related to the embodiment is included in at least one embodiment of this application. Therefore, "an embodiment" or "this embodiment" appearing throughout the specification does not necessarily refer to the same embodiment. Furthermore, these specific features, structures, or characteristics can be combined in any suitable manner in one or more embodiments.

[0026] Furthermore, reference numerals and / or letters may be repeated in different examples within this application. Such repetition is for the purpose of simplification and clarity and does not in itself indicate a relationship between the various embodiments and / or settings discussed.

[0027] In this article, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can mean: A exists alone, B exists alone, and A and B exist simultaneously. The term " / and" describes another type of relationship between related objects, indicating that two relationships can exist. For example, A / and B can mean: A exists alone, and A and B exist alone. In addition, the character " / " in this article generally indicates that the related objects before and after it have an "or" relationship.

[0028] In this article, the term "at least one" is merely a description of the relationship between related objects, indicating that there can be three relationships. For example, "at least one of A and B" can mean: A exists alone, A and B exist simultaneously, or B exists alone.

[0029] It should also be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion.

[0030] Example 1 This embodiment describes a method for preparing a two-atom nanozyme with a polygonal hollow carbon structure loaded with Cu and Pd. Please refer to the appendix. Figure 1 , Figure 1 This is a schematic flowchart of the preparation method of this application; The preparation method includes the following steps: Step S1: Dissolve 0.7 g of hydrazine monohydrate in 12 mL of methanol, and dissolve 1.5 g of 4-methylimidazole in 30 mL of methanol. After mixing, heat in an oil bath at 60 °C for 14 h with stirring. After naturally cooling to room temperature, let stand for 4 h, collect the solid by centrifugation, wash with methanol 3 times, and dry at 80 °C to obtain the organic ligand BIM. Step S2: Dissolve 3 mg of copper acetylacetonate, 1 mg of palladium acetylacetonate, 0.4 g of zinc nitrate hexahydrate, 20 mg of sodium formate, 5 mL of oleylamine, and 0.2 g of the BIM in 200 mL of N,N-dimethylformamide. Heat in an oil bath at 100°C with stirring for 48 h. After naturally cooling to room temperature, let stand for 4 h. Collect the solid by centrifugation, wash three times with N,N-dimethylformamide, and dry at 80°C to obtain the precursor STU1-b. Step S3: Heat the precursor STU1-b to 700℃ for 6 h under an argon atmosphere, allow it to cool naturally, and then grind it to obtain CuPd. SF / YSHNC nanozyme.

[0031] Example 2 Take the CuPd prepared in Example 1 SF / YSHNC nanozymes were observed for their morphology, size, and distribution using transmission electron microscopy (TEM) on CuPd. SF The elemental distribution of / YSHNC nanozymes was observed by mapping analysis, and the elemental loading was observed by EDS analysis. See TEM observation results Figure 2 The nanomaterial has a polygonal hollow porous structure with an outer diameter of about 40-50 nm and an inner cavity diameter of about 15-20 nm.

[0032] See the mapping analysis results. Figure 3 The results showed that C, N, O, Cu, and Pd elements were present in CuPd. SFUniform distribution in / YSHNC.

[0033] EDS analysis results can be found in [link to EDS analysis]. Figure 4 The results showed that the sample contained C, N, O, Cu, and Pd elements, with atomic percentages of 89.30%, 3.84%, 7.55%, 1.48%, and 0.10%, respectively. These results further demonstrate that Cu and Pd have been successfully loaded onto the carbon structure.

[0034] The effect achieved in this embodiment is as follows: This embodiment proves that CuPd SF / YSHNC nanozymes have a polygonal hollow porous structure, and C, N, O, Cu, and Pd elements are uniformly distributed in CuPd. SF / YSHNC in.

[0035] Example 3 Based on Example 1, this example applies to CuPd SF / YSHNC nanozyme for BET analysis; See results Figure 5 The results showed that CuPd SF The / YSHNC nanozyme exhibits a relatively obvious adsorption-desorption hysteresis loop, a specific surface area of ​​895.5337 m² / g, and an average pore size of 7.69 nm, indicating that CuPd SF / YSHNC nanozymes have a large specific surface area and a hierarchical pore structure dominated by mesopores.

[0036] Example 4 Based on Example 1, this example applies to CuPd SF The POD-like activity of / YSHNC nanozymes was detected. Peroxidase-like (POD) activity was detected using the classic TMB (3,3',5,5'-tetramethylbenzidine) colorimetric method. In the presence of hydrogen peroxide (H₂O₂), nanozymes exhibiting POD-like activity catalyze the oxidation of colorless reduced TMB to blue oxidized TMB (oxTMB), which exhibits a characteristic absorption peak at 652 nm. The POD-like catalytic activity of the nanozyme can be quantitatively evaluated by monitoring changes in absorbance at 652 nm. Higher absorbance values ​​indicate stronger POD-like activity and a greater generation of hydroxyl radicals (·OH).

[0037] Test results refer to Figure 6 CuPd at different concentrations (0, 2.5, 5, 10, 15, 20 μg / mL) SFThe absorbance of the / YSHNC nanozyme at 652 nm showed a significant concentration-dependent increase. The absorbance was 0.17 in the 2.5 µg / mL group, rising to 0.25 in the 5.0 µg / mL group, further increasing to 0.48 in the 10 µg / mL group, reaching 0.70 in the 15 µg / mL group, and reaching 0.92 in the 20 µg / mL group. Compared with the blank control group, the absorbance of the 20 µg / mL group increased by 820%.

[0038] The effect achieved in this embodiment is as follows: This embodiment proves that CuPd SF / YSHNC nanozymes exhibit good POD-like activity and show a significant concentration dependence.

[0039] Example 5 Based on Example 1, this example uses a glutathione oxidase activity assay kit to detect the GSHOx-like activity of nanozymes. Six time monitoring points were set up, and the UV-Vis absorption spectra of the reaction system were recorded at 0 min, 2 min, 4 min, 6 min, 8 min and 10 min respectively.

[0040] CuPd SF The YSHNC nanozyme and GSH solution were mixed evenly in a buffer solution and incubated at room temperature to initiate the catalytic reaction. Samples were taken at 0, 2, 4, 6, 8 and 10 minutes of the reaction, and the absorption spectra were recorded in the wavelength range of 300~600 nm using a UV-Vis spectrophotometer. The absorbance value at 412 nm was read.

[0041] The UV-Vis absorption spectra of the reaction system in the wavelength range of 300-600 nm at different reaction times are as follows: Figure 7 As shown, the absorbance at 412 nm was highest at the initial reaction time (0 min). As the reaction time increased from 0 min to 10 min, the absorbance at 412 nm gradually decreased, showing a clear time-dependent decreasing trend. Compared with the initial reaction time (0 min), the absorbance at 412 nm in the 10 min treatment group decreased by 44%.

[0042] Evaluation of CuPd nanozymes using a GSH kit SF / YSHNC's ability to digest glutathione (GSH) in bacteria. Results are as follows: Figure 8 As shown, CuPd is added SF The GSH level in bacteria after the / YSHNC nanozyme reaction decreased by about 30% compared with the control group and by about 22.2% compared with the Cu / YSHNC group.

[0043] The results achieved in this embodiment are as follows: The results of this embodiment show that CuPdSF / YSHNC nanozymes exhibit excellent GSH-like activity, enabling them to efficiently consume intrabacterial GSH and thereby disrupt the redox homeostasis of bacteria.

[0044] Example 6 Based on Example 1, this example detects CuPd SF The in vitro antibacterial and anti-biofilm activities of / YSHNC nanozymes.

[0045] Reference Figure 9 The CuPd nanozyme at different concentrations was evaluated using the plate coating method. SF The bactericidal effect of / YSHNC on methicillin-resistant Staphylococcus aureus (MRSA) airborne bacteria. MRSA bacterial suspensions in the logarithmic growth phase were diluted and reacted with different concentrations of CuPd. SF / YSHNC nanozymes were mixed to achieve final concentrations of 0 μg / mL (blank control group), 2.5 μg / mL, 5 μg / mL, 10 μg / mL, 15 μg / mL, and 20 μg / mL, and incubated at 37℃ in a shaker for 2 hours. After incubation, 100 μL of each reaction solution was evenly spread onto LB agar plates, which were then inverted and incubated at 37℃ for 12–16 hours. Colonies grown on the plates were counted and photographed, and the antibacterial rate was calculated. The experimental results showed that as the nanomaterial concentration increased from 0 μg / mL to 20 μg / mL, the number of colonies decreased significantly in a concentration-dependent manner; at a concentration of 20 μg / mL, almost no colonies grew on the plates, and the sterilization rate was approximately 99.9%. This indicates that CuPd... SF / YSHNC nanozymes can efficiently kill MRSA, exhibiting excellent in vitro antibacterial activity.

[0046] The crystal violet staining method was used to evaluate different concentrations of CuPd nanozyme. SF The disruptive effect of / YSHNC on bacterial biofilm. Results are as follows. Figure 10 As shown, as the concentration of nanomaterials increased from 0 μg / mL to 20 μg / mL, the amount of residual biofilm gradually decreased. At 20 μg / mL, almost no obvious purple staining structure was observed, indicating that the biofilm was largely destroyed and the amount of residual biofilm was extremely low.

[0047] The effect achieved in this embodiment is as follows: This embodiment confirms that CuPd SF / YSHNC nanozymes can efficiently kill MRSA airborne bacteria under in vitro conditions, while effectively destroying MRSA biofilms.

[0048] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A diatomic nanozyme with a polygonal hollow carbon structure loaded with Cu and Pd, characterized in that, The diatomic nanozymes loaded with Cu and Pd have C, N, O, Cu and Pd elements uniformly distributed on them.

2. The polygonal hollow carbon structure-supported Cu and Pd diatomic nanozyme according to claim 1, characterized in that, The atomic percentage of C in the Cu and Pd loaded diatomic nanozymes is 85%~95%, the atomic percentage of N is 2%~6%, the atomic percentage of O is 5%~10%, the atomic percentage of Cu is 1%~3%, and the atomic percentage of Pd is 0.05%~0.3%.

3. A polygonal hollow carbon structure-supported Cu and Pd diatomic nanozyme according to claim 1 or 2, characterized in that, The Cu and Pd loaded diatomic nanozyme has a polygonal hollow porous structure. The nanozyme has an outer diameter of 40-50 nm and an inner diameter of 15-20 nm. The specific surface area of ​​the nanozyme is 800-1000 m² / g.

4. The polygonal hollow carbon structure-supported Cu and Pd diatomic nanozyme according to claim 3, characterized in that, The Cu and Pd loaded diatomic nanozymes have at least one of POD-like activity and GSHOx-like activity.

5. A method for preparing a polygonal hollow carbon structure loaded with Cu and Pd diatomic nanozyme according to claims 1-4, characterized in that, Includes the following steps: Step S1: Dissolve 0.5-1.0 g of hydrazine monohydrate in 10-15 mL of methanol, and dissolve 1.5-2.0 g of 4-methylimidazole in 30-40 mL of methanol. After mixing, heat in an oil bath at 55-75℃ with stirring. After naturally cooling to room temperature, let stand for 2-6 h, collect the solid by centrifugation, wash with methanol, and dry to obtain the organic ligand BIM. Step S2: Dissolve 3-5 mg of copper acetylacetonate, 1-3 mg of palladium acetylacetonate, 0.4-0.8 g of zinc nitrate hexahydrate, 20-40 mg of sodium formate, 5-10 mL of oleylamine, and 0.2-0.5 g of the BIM in 200-300 mL of N,N-dimethylformamide. Stir and heat in an oil bath, allow to cool naturally to room temperature, and let stand for 2-6 h. Collect the solid by centrifugation, wash with N,N-dimethylformamide, and dry to obtain the precursor STU1-b. Step S3: After heat treatment of the precursor STU1-b, it is naturally cooled and then ground to obtain the Cu and Pd loaded diatomic nanozyme.

6. The method for preparing a polygonal hollow carbon structure loaded with Cu and Pd diatomic nanozyme according to claim 5, characterized in that, In step S1, the oil bath stirring and heating time is 12-18 hours, and the drying temperature is 60-100℃.

7. The method for preparing a polygonal hollow carbon structure loaded with Cu and Pd diatomic nanozyme according to claim 5, characterized in that, In step S2, the oil bath temperature is 100-120℃, the oil bath stirring and heating time is 48-72 h, and the drying temperature is 60-100℃.

8. The method for preparing a polygonal hollow carbon structure loaded with Cu and Pd diatomic nanozyme according to claim 5, characterized in that, The heat treatment conditions in step S3 are as follows: under an argon atmosphere, the heat treatment temperature is 600-900℃, and the heat treatment time is 4-8 h.

9. The method for preparing a polygonal hollow carbon structure loaded with Cu and Pd diatomic nanozyme according to claim 5, characterized in that, In step S1, the methanol washing is performed 3-5 times; in step S2, the N,N-dimethylformamide washing is performed 3-5 times.

10. The use of the Cu and Pd loaded diatomic nanozyme prepared by any one of claims 5-9 in the preparation of a drug for treating drug-resistant bacterial osteomyelitis.

Citation Information

Patent Citations

  • Nano-carbon-loaded palladium-iron bimetallic cluster nano-enzyme as well as preparation method and application thereof

    CN113786843A

  • Preparation method of FeZn-N-C monatomic nano-enzyme and composite nano-enzyme

    CN117860780A